Performance of Rotation‐Symmetric Bosonic Codes in a Quantum Repeater Network - Li, Pei‐Zhe; Dias, Josephine; Munro, William J.; van Loock, Peter; Nemoto, Kae; Lo Piparo, Nicoló (Advanced Quantum Technologies, 2024)
Quantum error correction codes based on continuous variables play an important role for the implementation of quantum communication systems. A natural application of such codes occurs within quantum repeater systems which are used to combat severe channel losses and local gate errors. In particular, channel loss drastically reduces the distance of communication between remote users. Here, a cavity-quantum electrodynamics (QED) based repeater scheme is considered to address the losses in the quantum channel. This repeater scheme relies on the transmission of a specific class of rotationally invariant error-correcting codes. Several rotation-symmetric bosonic codes (RSBCs) are compared for encoding the initial states of two remote users connected by a quantum repeater network against the convention of the cat codes and the performance of the system is quantified by using the secret key rate. In particular, the number of stations required to exchange a secret key over a fixed distance is determined and establish the resource overhead. For higher-loss codes, the results show that a secret key rate (SKR) value of 0.01 bit per channel use can be achieved at a distance of 10000 km, with an elementary distance of 1.3 km.<br